2021
DOI: 10.34172/ijhpm.2021.126
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Hepatitis B Mass Screening and Management in High-Prevalent Rural China: A Model Study From 2020 to 2049

Abstract: Background: Chronic hepatitis B is highly prevalent among adults in rural China and better management of those populations is of vital importance for viral hepatitis elimination. Adult immunization has been the subject of much controversy in previous studies. This study estimates the cost-effectiveness of population-based hepatitis B screening, treatment, and immunization strategy (comprehensive strategy) in rural areas with high prevalence under the national policy of sharp-drop drug prices. Methods: We const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The modeling studies of China showed that launching an extensive adult HBV infection screening and vaccination program can effectively reduce incidence and mortality, and it is cost-effective [10,11]. Our research provides real-world evidence for this.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The modeling studies of China showed that launching an extensive adult HBV infection screening and vaccination program can effectively reduce incidence and mortality, and it is cost-effective [10,11]. Our research provides real-world evidence for this.…”
Section: Discussionmentioning
confidence: 59%
“…In 2016, a modeling study in China reported that HBV infection screening and hepatitis B vaccination in adults aged 21-39 years can prevent 1.9 million HBV infections and 56,000 HBV-related early deaths [10]. Another modeling study in 2021 in China has revealed that HBV infection screening and hepatitis B vaccination for adults yield 18.08 life years and 17.46 qualityadjusted life years [11]. However, the evidence for the effectiveness of such public health projects funded by the government is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…The same vaccination program was also piloted in Keqiao and Tonglu. Our previous economic analysis based on the Markov model has demonstrated that population-based immunization could prevent most new HBV infections if all susceptible individuals were vaccinated and this strategy was cost-effective [ 25 ]. However, the interventions may have little impact when HBV incidence has dropped to a lower level and the incidence reached a plateau in the last round.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the prevention and control of HBV infection in high-prevalence areas was still challenging. Screening HBV infection and immunization for young adults have been proved to be cost-effective in China [ 25 , 43 ]. Free vaccination could be considered for susceptible adults to avoid new infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation